Stochastic and sinusoidal electrical stimuli increase the irregularity and gain of Type A and B medial vestibular nucleus neurons, in vitro. Issue 11 (12th September 2021) - Stefani, Sebastian P.; Pastras, Christopher J.; Serrador, Jorge M.; Breen, Paul P.; Camp, Aaron J.
Abstract: Galvanic vestibular stimulation (GVS) has been shown to improve vestibular function potentially via stochastic resonance, however, it remains unknown how central vestibular nuclei process these signals. In vivo work applying electrical stimuli to the vestibular apparatus of animals has shown changes in neuronal discharge at the level of the primary vestibular afferents and hair cells. This study aimed to determine the cellular impacts of stochastic, sinusoidal, and stochastic + sinusoidal stimuli on individual medial vestibular nucleus (MVN) neurons of male and female C57BL/6 mice. All stimuli increased the irregularity of MVN neuronal discharge, while differentially affecting neuronal gain. This suggests that the heterogeneous MVN neuronal population (marked by differential expression of ion channels), may influence the impact of electrical stimuli on neuronal discharge. Neuronal subtypes showed increased variability of neuronal firing, where Type A and B neurons experienced the largest gain changes in response to stochastic and sinusoidal stimuli. Type C neurons were the least affected regarding neuronal firing variability and gain changes. The membrane potential (MP) of neurons was altered by sinusoidal and stochastic + sinusoidal stimuli, with Type B and C neuronal MP significantly affected. These results indicate that GVS‐like electrical stimuli impact MVN neuronal discharge differentially, likely as a result of heterogeneous ion channel expression. Abstract : Stochastic and sinusoidal stimuli shown to increase neuronal discharge irregularity and gain in Type A and B medial vestibular nucleus (MVN) neurons. Potentially via antagonism of voltage‐sensitive channels expressed on MVN neuronal membranes such as the large conductance K + channels ( black ) and associated N‐type Ca 2+ channels, and the T‐type Ca 2+ channels associated with slow conductance K + channels ( gray ).